2021
DOI: 10.1186/s40561-021-00172-9
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of Chinese students' behavioral intentions to adopt 5G for smart-learning in Covid-19

Abstract: The social distancing due to the Covid-19 epidemic has disturbed all sectors of society, including education. To maintain normal operations, it is necessary to adapt quickly to this situation. Many technologies and platforms have rushed to offer their support to users. This article adopts a critical perspective to reflect on the factors that may cause the hasty adoption of 5G smart learning technology. To investigate students' intentions toward smart learning, this article provides a theoretical framework prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…In this study, the target group is students from Gannon University. Similar work is presented in studies by Al-Maroof et al (Al-Maroof et al, 2021) and Shah et al (Shah et al, 2021), which have considered students from gulf countries, China, and Iran, respectively. All studies have considered the technology acceptance model with additional factors.…”
Section: Related Worksupporting
confidence: 68%
“…In this study, the target group is students from Gannon University. Similar work is presented in studies by Al-Maroof et al (Al-Maroof et al, 2021) and Shah et al (Shah et al, 2021), which have considered students from gulf countries, China, and Iran, respectively. All studies have considered the technology acceptance model with additional factors.…”
Section: Related Worksupporting
confidence: 68%
“…A further solution could be the widespread deployment of 5G to ensure adequate internet connectivity, in which policy makers, service providers and educational institutions should work together (Shah et al, 2021). König and colleagues found that teachers who kept in regular contact with their students and their parents and used effective and modern educational software and platforms were more effective in online education than teachers who did not.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Various applications of 5G technology in devices and equipment are of interest to researchers. Examples of the study of consumer attitudes towards 5G technology include smart mobiles (Yu & Jin, 2021); smart university campus (Martinez et al, 2021); smart learning technology (Shah et al, 2021a); smart home and Internet of Things (Korneeva et al, 2021;Singh et al, 2018) and healthcare solutions (Rahman et al, 2022),…”
Section: Introductionmentioning
confidence: 99%